2006
DOI: 10.3189/172756406781812050
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the response of glacier systems to climate warming in China

Abstract: ABSTRACT. A glacier system is regarded as the ensemble of many glaciers sharing the same region, influenced by a similar climate and organized by certain intrinsic laws. It can be either 'sensitive' or 'steady'. On the basis of the structure of the glacier system and the nature of the equilibrium-line altitudes at the steady state, functional models of a glacier system responding to climate warming were established, using the Kotlyakov-Krenke equation relating annual glacier ablation and mean summer temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 4 publications
0
27
0
1
Order By: Relevance
“…In semi-distributed models, glacier systems are represented by glacier areaaltitude distribution histograms of subbasins, typically with a step of 100 m (Dyurgerov et al 1995;Tangborn and Rana 2000;Alford et al 2009;Hagg et al 2011;Bocchiola et al 2011). An alternative approach is to represent a glacier (sub-) system by its overall area and mean ELA (Aizen and Loktionova 1996;Aizen 1996, 1998;Konovalov 1997;Lebedeva 1997;Shetinnikov 1998;Xie et al 2006;Kang et al 2009). Fully distributed models (IrvineFynn et al 2012;Boscarello et al 2012) are rare, since up-scaling glacier areal parameters is a challenging task for basins with a large number of glaciers, most of which are of subgrid size.…”
Section: Methods Of Meltwater Assessments: a Reviewmentioning
confidence: 99%
“…In semi-distributed models, glacier systems are represented by glacier areaaltitude distribution histograms of subbasins, typically with a step of 100 m (Dyurgerov et al 1995;Tangborn and Rana 2000;Alford et al 2009;Hagg et al 2011;Bocchiola et al 2011). An alternative approach is to represent a glacier (sub-) system by its overall area and mean ELA (Aizen and Loktionova 1996;Aizen 1996, 1998;Konovalov 1997;Lebedeva 1997;Shetinnikov 1998;Xie et al 2006;Kang et al 2009). Fully distributed models (IrvineFynn et al 2012;Boscarello et al 2012) are rare, since up-scaling glacier areal parameters is a challenging task for basins with a large number of glaciers, most of which are of subgrid size.…”
Section: Methods Of Meltwater Assessments: a Reviewmentioning
confidence: 99%
“…The most widely used hydrological models, such as the distributed SWAT, the MIKE-SHE model and the conceptual SRM model, as a rule do not calculate glacier melt processes, despite the fact that excluding the glacier processes could induce large errors in glacierized catchments. Glacier processes are complex in that glacier melt will at first increase due to the rise in ablation and lowering of glacier elevation, and then, after reaching its peak, will decrease due to the shrinking in glacier area (Xie et al, 2006). Moreover, simulation errors can be re-categorized as precipitation or glacier meltwater and consequently result in a greater uncertainty in the water balance in high mountain areas .…”
Section: Glacier Melt Modelingmentioning
confidence: 99%
“…Shi and Liu (2000) estimated that by 2100, glacier volume in China may be only 30-67 % than that of the present day. Xie et al (2006) simulated scenarios in which temperatures warmed by 0.01, 0.03, and 0.05 K a -1 and found that by the end of the twenty-first century, China's glaciated areas would decrease by 14, 40, and 60 %, respectively.…”
mentioning
confidence: 99%